Solidarity in spaces of ‘care and custody’: The hospitality politics of immigration detention visiting - Kemp, Tom (Theoretical criminology, 2021)
This article contributes to criminological understanding of immigration detention by highlighting volunteer visiting as a space of embodied thinking about critical responses to the burgeoning crimmigration system. It draws from interview material with volunteer visitors and people held in immigration detention centres to assess conceptual relevance of critical hospitality studies for anti-border practice. Both within Derridean scholarship on hospitality and in social-discourses on migration, host/citizen and guest/migrant identifications are understood as stable subject positions. I argue that to support resistance to deportation and establish mutual solidarity and cooperation in this context, detention visitors adopt multiple strategies of hospitality that position themselves as visitors as well as hosts. By counter-posing differing ways that volunteers occupy these roles, I show how the copresence of divergent ways of offering hospitality allows visitors to navigate the complicities that necessarily afflict support in solidarity with migrants in carceral spaces of border control.